‘From Sanctuary to Welcoming Cities’: Negotiating the Social Inclusion of Undocumented Migrants in Liège, Belgium - Lambert, Sébastien (Social Inclusion, 2019)
Cities have become important sites of sanctuary for migrants with a precarious legal status. While many national governments in Europe have adopted restrictive immigration policies, urban governments have undertaken measures to safeguard undocumented residents’ rights. Existing scholarship on sanctuary cities has mostly focused on how cities’ stance against federal immigration policies can be interpreted as urban citizenship. What is largely missing in these debates, however, is a better insight into the role that local civil society actors play in pushing for sanctuary and negotiating the terms of social in- and exclusion. In this article, we rely on a qualitative study of the 2017 Sanctuary City campaign in Liège, Belgium, to argue that power relations between (and among) civil society actors and city officials help to explain why the meaning and inclusiveness of ‘sanctuary’ shifted over time. Initially, radical activists were able to politicize the issue by demanding the social inclusion of the ‘sans-papiers’ through grassroots mobilization. However, the cooptation of the campaign by immigrant rights organizations led to the adoption of a motion wherein the local government depicted the city as a ‘welcoming’ instead of a ‘sanctuary’ city. By showing how immigrant rights professionals sidelined radical activists during the campaign, we highlight the risk of depoliticization when civil society actors decide to cooperate with local governments to extend immigrant rights. We also underline the potential representational gap that emerges when those who are directly implicated, namely undocumented migrants, are not actively involved in campaigns that aim to improve their inclusion.